Feminist Activism, Travel and Translation Around 1900 Transnational Practices of Mediation and the Case of Käthe Schirmacher - Gehmacher, Johanna (2024)
This study examines the 'travel' of political concepts between women's movements in the West around 1900 and argues that for the historical analysis of social movements, regardless of whether they were transnationally active or not, the exploration of the transfer practices that create spaces of exchange across linguistic and other borders is of eminent importance. It takes the biographical case of German feminist Käthe Schirmacher to explore political travelling, transnational journalism and translation as forms of transfer within and between social and political movements. The book analyses the political and pragmatic contexts of activist translation, discussing practices such as the rendering of political and literary texts, interpreting at transnational meetings and translating excerpts from foreign-language activist literature.